Natural Ventilation Performance for Schools During a Pandemic and the Post-Pandemic COVID 19 - Dyah Hendrawati (Departement of Architecture, Universitas Islam Indonesia, 2021)
Natural ventilation is applied to most educational buildings in Indonesia. Natural ventilation is one of the strategies to achieve the physical comfort of residents and an effort to save energy. During a pandemic, natural ventilation requires because it is expected to make the air circulation in the room. The presence of good air circulation will make the spread of the virus can be avoided. One indicator of the success of space for good and healthy air circulation is the achievement of Air Change per Hours (ACH) values according to standards. The study aims to find out and identify the performance of natural ventilation as an element that determines indoor air circulation against the spread of the covid 19 viruses, comfortable air velocity in a room and user capacity. The study used simulation methods to determine the value of ACH and air velocity. The research main goal was to look at the possibility of reopening schools as safely and quickly as possible. The results showed that the school buildings studied could be used for Pandemic and postpandemic times, indicated by ACH grades > 8 and air velocity in room 0.2-0.8 m/s. The building has an opening area of approximately 30% with an opening type that is able 45% wind flow. With the simulation obtained, to achieve health and comfort standards with 50% users, with certain air velocity conditions, the minimum opening area is 20% with 45% aperture type and 90% type.Keywords: ACH; natural ventilation; performance; window types